The Making of Tablighi Female Ulama a Case Study of Pesantren Dar El-Wihdah Sragen in Achieving SDGs - Syarifah Isnaini; Sekar Ayu Aryani (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study explores the process of forming and educating Tablighi female ulama at Pesantren Dar El-Wihdah, Sragen, and examines its contribution to achieving the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 5 (Gender Equality), and SDG 16 (Peace, Justice, and Strong Institutions). The primary objective of this research is to analyze how an Islamic boarding school affiliated with the Tablighi Jamaat develops women religious scholars who are capable of engaging in da‘wah and community leadership. Theoretical framework: The theoretical framework draws on gender studies in Islamic education, social reproduction theory, and religious authority, emphasizing women’s access to knowledge and public religious roles. Literature review: The literature review indicates that previous studies on Tablighi Jamaat largely focus on male dominance in public preaching and highlight limited educational opportunities for women, often confining them to domestic or supportive roles. Research on Tablighi women’s education generally suggests insufficient preparation for independent da‘wah and scholarly authority. Methods: Addressing this gap, this study employs an ethnographic methodology, using participant observation and in-depth semi-structured and unstructured interviews with female santri, teachers, and pesantren leaders. Results: The findings reveal that Pesantren Dar El-Wihdah implements a systematic cadreization of female ulama through character-building programs, intensive mastery of classical Islamic texts (kutub turath), and structured training using Tablighi Jamaat manuals. Furthermore, the establishment of Rumah Qur’an (Ruqun) and Marhalah Ta‘lim Aly strengthens pedagogical quality and enhances women’s preaching skills and social engagement. These initiatives enable female santri to actively participate in religious dissemination and community interaction beyond the pesantren environment. Implications: The implications of this study demonstrate that faith-based educational institutions can significantly contribute to SDGs by promoting inclusive religious education and empowering women as agents of social and moral development. Novelty: The novelty of this research lies in highlighting an alternative model of Tablighi Jamaat education that successfully produces female ulama with scholarly legitimacy and public religious authority, challenging the prevailing male-centered narrative within the movement.